The relationship between urinary iodine concentration and papillary thyroid cancer: A systematic review and meta-analysis - Zhang, Xueqi; Zhang, Fan; Li, Qiuxian; Aihaiti, Renaguli; Feng, Chuyao; Chen, Deshi; Zhao, Xu; Teng, Weiping (Frontiers in Endocrinology, 2022)
Background: The effect of iodine on papillary thyroid cancer (PTC) has been controversial for many years. Since urinary iodine is an effective indicator of iodine intake, some recent epidemiological studies have described the relationship between urinary iodine concentration (UIC) and PTC. Methods: We searched PubMed, Embase, Cochrane Library, and Web of Science for case-control studies about UIC and PTC published before September 2022. Results are presented as the overall odds ratio (OR) and 95% confidence intervals (CI). Results: According to the analysis of the included studies, excessive iodine intake (UIC≥300ug/L) was positively associated with the occurrence of PTC patients compared with healthy controls (OR4.05, 95%CI 1.64-10.02, P=0.002). Meanwhile, adequate iodine exposure (100≤UIC<200ug/L) may play a protective role in the occurrence of PTC compared with healthy individuals (OR 0.36, 95%CI 0.14-0.91, P=0.03) while the difference in the prevalence of insufficient iodine intake (UIC<100ug/L) and iodine above requirements (200≤UIC<300ug/L) among the two groups were not significant (deficiency: OR 0.38, 95%CI 0.13-1.16, P=0.09; above requirements: OR 0.92, 95%CI 0.40-2.10, P=0.84). After comparing the UIC levels of PTC patients with those of other thyroid diseases, we found that there was also no significant difference in the incidence of different levels of UIC in the two groups (excessive: OR 1.25, 95%CI 0.87-1.80, P=0.22; above requirements: OR 0.93, 95%CI 0.77-1.14, P=0.49; adequate: OR 0.96, 95%CI 0.78-1.17, P=0.67; deficiency: OR 1.02, 95%CI 0.86-1.22, P=0.80). The result of this meta-analysis also did not support the relationship between UIC and the BRAF mutation and lymph node metastasis (LNM) of PTC patients. Besides, we also found that studies on the relationship between urinary iodine and PTC may be influenced by the way UIC was measured. Conclusion: The 10 case-control included studies involved a total of 6,544 participants. The results of this meta-analysis showed excessive iodine intake, that is, UIC≥300ug/L was associated with the occurrence of PTC but not with BRAF mutation and LNM while adequate iodine intake (100≤UIC<200ug/L) may be one of the protective factors for PTC.